Foundations of software science and computational structures 14th International Conference, FOSSACS 2011, held as part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2011, Saarbrücken, Germany, March 26-April 3, 2011. Proceedings - Hofmann, Martin (LNCS sublibrary. SL 1, Theoretical computer science and general issues, 2011)
This book constitutes the refereed proceedings of the 14th International Conference on Foundations of Software Science and computational Structures, FOSSACS 2011, held in Saarbrücken, Germany, March 26?April 3, 2011, as part of ETAPS 2011, the European Joint Conferences on Theory and Practice of Software. The 30 revised full papers presented together with one full-paper length invited talk were carefully reviewed and selected from 100 submissions. The papers are organized in topical sections on coalgebra and computability, type theory, process calculi, automata theory, semantics, binding, security, and program analysis.